Bases bioquímicas da interação do cajueiro anão precoce com o fungo Lasiodiplodia theobromae causador da resinose - Gondim, Darcy Mayra Furtado (2010)
In Brazil, the cashew (Anacardium occidentale L.) crop stands out for large cultivated area and high nut yield, with the state of Ceara in the level of the main national producer and exporter. Several diseases infect the cashew plant, causing huge economic losses. Among them, the gummosis caused by the fungus Lasiodiplodia theobromae, is currently the most important disease of cashew in the semi-arid conditions of north-eastern Brazil. This study aimed to detect biochemical differences between two cashew clones, CCP 76 and BRS 226, respectively, susceptible and resistant to gummosis, in order to understand the cashew defense mechanisms against the infection by this fungus. All tests were performed on stem tissue, the local of primary infection, both in healthy plants and the infected by the pathogen in different periods after infection. Two different approaches were used: first, a detection of-various compounds (phenols, tannins and hydrogen peroxide) and enzymes (superoxide dismutase, ascorbate peroxidase, catalase, guaiacol peroxidase, phenylalanine ammonia lyase, 03-1, 3- glucanase and chitinase) related to plant defense was made; in a second stage, a proteomic study was done by performing two-dimensional electrophoresis followed by identification of the proteins of interest by mass spectrometry and bioinformatics tools. Our results show that the two antifungal enzymes analyzed, glucanase and chitinase, accumulated differentially in contrasting clones. Higher activities of these enzymes, especially chitinase, were observed in the resistant clone, both in recent times after infection in seedlings, and in advanced stages of gummosis in adult plants grown in the field. Also, there is evidence that susceptible clone accumulated more H202, thus facilitating the establishment of this pathogen, which has necrotrophic habits. With regard to proteomic analysis, was first established an effective protocol for protein extraction of cashew stem, a highly recalcitrant plant tissue. Through the techniques of two-dimensional electrophoresis, mass spectrometry (nano-ESIUPCL-Q-TOF) and bioinformatics tools allowed the identification of 59 different spots in samples from branches of adult plants. Approximately 50% of these spots are proteins related to stress responses: heat shock proteins (sHSPs), superoxide dismutase, 0-1,3-glucanase, isoflavone reductase, peroxidase, catalase, ascorbate peroxidase, and others. This result is consistent with the excellent fit of cashew to the semi-arid. This information applies mainly to clones CCP 76 and BRS 226, since both have good productivity in this adverse climate. Several differentially expressed proteins were detected. The identity-of some of them- were shown to be sHSPs, superoxide dismutase, 13-1 ,3-glucanase and guaiacol peroxidase and ascorbate. However, the increase in these proteins occurred in both the resistant and susceptible clone, and is not therefore possible to correlate them with the characteristic resistance of cashew BRS 226. Further studies demonstrated the temporal expression of these proteins may allow new conclusions about the interaction cashew-L. theobromae. This is the first study that aimed to discover molecules that are linked to the defense response of cashew in response to infection by L. theobromae.